2020
DOI: 10.4149/neo_2020_190723n657
|View full text |Cite
|
Sign up to set email alerts
|

The long non-coding RNA PVT1/miR-145-5p/ITGB8 axis regulates cell proliferation, apoptosis, migration and invasion in non-small cell lung cancer cells

Abstract: Lung cancer is one of the leading causes of death worldwide and non-small cell lung cancer (NSCLC) accounts for approximately 80% of lung cancer. Long noncoding RNAs (lncRNAs) are closely associated with the development and progression of various cancers, including lung cancer. The purpose of this study was to explore the potential role and molecular mechanism of lncRNA plasmacytoma variant translocation 1 (PVT1) in regulating the proliferation, apoptosis, migration, and invasion of NSCLC cells. The expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…According to existing literature, miR-145-5p in NSCLC has been reported to be regulated by multiple long-chain non-coding RNAs, including SNHG1, JPX and PVT1. These long-chain non-coding RNAs have been revealed to exhibit cancer-promoting effects in NSCLC by enhancing the expression of downstream coding genes via sponging miR-145-5p (19)(20)(21). At present, studies on whether miR-145-5p is regulated by circRNAs in NSCLC are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…According to existing literature, miR-145-5p in NSCLC has been reported to be regulated by multiple long-chain non-coding RNAs, including SNHG1, JPX and PVT1. These long-chain non-coding RNAs have been revealed to exhibit cancer-promoting effects in NSCLC by enhancing the expression of downstream coding genes via sponging miR-145-5p (19)(20)(21). At present, studies on whether miR-145-5p is regulated by circRNAs in NSCLC are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…The DEGs (p value < 0.05, fold change > 1.5) in AM_EC versus AM_EM are presented as volcano maps, and analysis of the upregulated genes with log 2 fold change > 1 showed that the functions of a series of genes were related to angiogenesis (such as MMP1 and ESM1), in ammation (such as CXCL8 [26]) and cell motility (such as ITGA2 [27] and ITGB8 [28]) (Fig. 3D).…”
Section: Resultsmentioning
confidence: 99%
“…PRKCZ antisense RNA 1 (PRKCZ-AS1) led to enhanced mitogen-activated protein kinase (MAPK) signaling by inhibiting mir-766-5p and increasing its target MAPK1 to enhance NSCLC proliferation and migration [76]. PVT1 can also regulate activation of MAPK signaling by sponging miR-145-5p and increasing integrin subunit beta 8 (ITGB8), as well as activate the wingless (Wnt)/β-catenin pathway by sponging mir-361 and increasing SRY-box transcription factor 9 (SOX9) for enhanced NSCLC tumorigenesis [82,83]. As discussed previously, PVT1 was shown to have roles in cell-cycle regulation and the regulation of proteins for invasion and migration and, therefore, be a promising therapeutic target due to its multiple functions in NSCLC progression.…”
Section: Regulation Of Key Oncogenic Signaling Pathwaysmentioning
confidence: 99%